Amniocentesis in HIV Pregnant Women: 16 Years of Experience - Mafalda Simões; Catarina Marques; Ana Gonçalves; Ana Paula Pereira; Joaquim Correia; João Castela; Cristina Guerreiro (Hindawi Limited, 2013)
The iatrogenic risk of HIV vertical transmission, calculated in initial epidemiologic studies, seemed to counterindicate invasive prenatal diagnosis (PND) procedures. The implementation of highly active antiretroviral therapy (HAART) represented a turning point in PND management, owing to a rapid and effective reduction of maternal viral load (VL). In the present study, we identified cases of vertical transmission in HIV-infected pregnant women who did amniocentesis in the second trimester of pregnancy (), from 1996 to 2011. We divided our sample into Group A-women under HAART when submitted to amniocentesis () and Group B-women without antiretroviral therapy before amniocentesis (). We had 1 case of vertical transmission in Group B. Preconceptional or early first trimester HIV serology is essential to avoid performing an amniocentesis without antiretroviral therapy or viral suppression. When there is an indication for amniocentesis in an HIV-infected pregnant woman, it should be done if the patient is on HAART and, if possible, when VL is undetectable. Nowadays, with combined first trimester screening test to select pregnancies with high risk of aneuploidies, advanced maternal age is a less frequent indication to perform PND invasive procedures, representing an outstanding gain in prenatal diagnosis of this population.